REVIEW OF COFFEE MARKETING STRATEGIES IN BUSINESS COMPETITION - Mrs Fadillah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Increasing competition tension cannot be avoided. Information disclosure and the rapid pace of technology are the way. Developing a digital marketing strategy is a necessity. For those reason, this study aims to analyze several marketing strategies were compatible with the digital era. The research method used is descriptive qualitative, using three-stage decision, namely EFE Matrix, Competitive Matrix (CPM), IFE Matrix. Then the second stage is matching; SWOT Matrix and Big Strategy Matrix. The last stage is the Quantitative Strategic Planning Matrix (QSPM). The position of companies located in quadrant II needs to seriously evaluate their approach to the market. Even though their industry is growing, they cannot compete effectively, and they need to find out why the company's current approach is not effective and how companies can improve their competitiveness. In evaluating marketing strategies, the author analyzes the sustainability of the company. Based on the results of the above analysis, it is expected that a strategy that must be implemented by PT. Nedcoffe